Inhibition of Akt/mTOR Attenuates Age‐Related Changes in Mesenchymal Stem Cells. (15th July 2014) - Gharibi, Borzo; Farzadi, Samira; Ghuman, Mandeep; Hughes, Francis J.
Abstract The decline in mesenchymal stem cell (MSC) self‐renewal and function with aging contributes to diseases associated with impaired osteogenesis. MSC donor age in prolonged culture also limits the therapeutic potential of these cells for tissue engineering and regenerative medicine. Here, we demonstrate an intervention to preserve the immature state MSC and consequently maintain self‐renewal and differentiation capacity during in vitro aging. We showed that blocking of phosphatidylinositol 3‐kinase/Akt/mammalian target of rapamycin (mTOR) prevents the development of an age‐related phenotype and maintains MSC morphology of early passage cells with high clonogenic frequency and enhanced proliferative capacity. MSC cultured in the presence of inhibitors of Akt or mTOR also robustly maintain their osteogenic potential, that is otherwise lost during in vitro aging. We further report that these effects may be mediated by induction of expression of pluripotency genes Nanog and Oct‐4 and by the reduction in the production of cytoplasmic reactive oxygen species (ROS). Additionally, loss of Akt/mTOR and ROS was accompanied with lower levels of DNA damage. These results provide an insight into mechanisms involved in MSC aging and suggest possible interventions to maintain quiescence and function of MSC prior to in vivo transplantation or as pharmacological agents in diseases associated with loss of MSC function. Stem Cells2014;32:2256–2266